Bias reduction with Variable Percent Bias Reducing matching - Yatracos, Yannis G. (My University, 2016)
The bias in linear combinations, a'X, of treatment and control X-covariates obtained with EPBR matching can be reduced when all a-coordinates have same sign, using Variable Percent Bias Reducing (VPBR) matching for selected X-covariates' subgroups. For specified subsets of a-values, VPBR matching reduces the absolute bias.
Keywords: Bias reduction; Matching